Understanding the Influences of Hedonic Personality towards Advertising Avoidance on Social Media - Desmonda, Diera; Jimmy, So Yohanes; Annas, Mohammad (The South East Asian Journal of Management, 2024)
Research Aims: This study aims to investigate and explore how the hedonic personality that exists in each individual can influence avoidance behaviour towards advertisements on social media platforms. Design/Methodology/Approach: A quantitative approach with a purposive sampling technique was employed to collect data from 198 respondents who have shopped or at least searched for products on social media. The data were then analysed using the Structural Equation Modelling (SEM) technique. Research Findings: The results showed that hedonic personality affected advertising avoidance behaviour. Through multigroup analysis, this research found differences in how men and women respond to an advertisement. On the other hand, the intrusive level of an advertisement had a direct effect on ad avoidance behaviour on social media. Theoretical Contribution/Originality: This study contributes knowledge by exploring and linking hedonic personality with ad avoidance behaviour. In addition, this study analyses how those relationships are different between men and women. Managerial Implication in the South East Asian Context: The results of this study are expected to provide insights for advertisers and encourage them to consider the hedonic style when determining the target customers. Also, the results inform that the model or ad content should be differentiated when targeting men or women. Research Limitation & Implications: This study is limited in several ways, such as the demographic reach and number of respondents. Additionally, the number of social media platforms is only limited to Instagram and Facebook.